Pengelolaan dan Pengembangan Lay Pengelolaan dan Pengembangan Layanan Bimbingan Konseling di Institusi Pendidikan - Auliana Utami, Chadiza (Science and Education Journal (SICEDU), 2024)
This study aims to examine the management and development of guidance and counseling services in educational institutions through a literature study approach. The main issues raised include challenges in organizing guidance and counseling, effective management efforts, and service development strategies that can improve the quality of guidance in schools. In this context, guidance and counseling is considered as one of the important aspects in supporting student development, both in academic, social, and psychological domains. The method used in this study is a literature study, namely by collecting, analyzing, and interpreting literature related to the management and development of guidance and counseling services in educational institutions. Data were obtained from various library sources, such as books, scientific journals, and articles that are relevant to this topic. The results of the study indicate that the management of guidance and counseling services needs to be supported by careful planning, involvement of various related parties, and training for counselors. In addition, the development of guidance and counseling services is expected to focus on innovation of methods and approaches that are more adaptive to student needs. These findings can be a reference for improving the quality of guidance and counseling services in educational institutions in the future.